Dracula (Oxford bookworms, ,, 1986)
Bram Stoker's novel became one of the masterpieces of the horror genre, brilliantly evoking a world of vampires and vampire hunters whilst simultaneously exposing the dark corners of Victorian sexuality and frustrated desire.

The curious incident of the dog in the night-time (Red Fox, Vintage Books, Vintage Digital, 2014)
A murder mystery like no other, this novel features Christopher Boone, a 15-year-old who suffers from Asperger's syndrome. When he finds a neighbour's dog murdered, he sets out on a journey which will turn his whole world upside down.

The handmaid's tale (The Handmaid's Tale, 1,, 2012)
Offred is a Handmaid in the Republic of Gilead. She has only one function: to breed. If she deviates, she will, like dissenters, be hanged at the wall or sent out to die slowly of radiation sickness. But even a repressive state cannot obliterate desire - neither Offred's nor that of the two men on which her future hangs.

Normal people (Faber & Faber, Clipper Audiobooks, 2019)
Connell and Marianne grow up in the same small town in rural Ireland. The similarities end there; they are from very different worlds. When they both earn places at Trinity College in Dublin, a connection that has grown between them lasts long into the following years. This is an exquisite love story about how a person can change another person's life - a simple yet profound realisation that unfolds beautifully over the course of the novel. It tells us how difficult it is to talk about how we feel and it tells us - blazingly - about cycles of domination, legitimacy and privilege. Alternating menace with overwhelming tenderness, Sally Rooney's second novel breathes fiction with new life.

Nineteen eighty-four (Penguin Book of the British Short Story, ,, 2012)
In Nineteen eighty-four , one of the 20th century's great myth-makers takes a cold look at the future. Orwell's study of individual struggling - or not struggling - against totalitarianism remains a salutary lesson in any society.

The shadow king (Canongate Books, Canongate, 2019)
ETHIOPIA. 1935. With the threat of Mussolini?s army looming, recently orphaned Hirut struggles to adapt to her new life as a maid. Her new employer, Kidane, an officer in Emperor Haile Selassie?s army, rushes to mobilise his strongest men before the Italians invade. Hirut and the other women long to do more than care for the wounded and bury the dead. When Emperor Haile Selassie goes into exile and Ethiopia quickly loses hope, it is Hirut who offers a plan to maintain morale. She helps disguise a gentle peasant as the emperor and soon becomes his guard, inspiring other women to take up arms. But how could she have predicted her own personal war, still to come, as a prisoner of one of Italy?s most vicious officers? The Shadow King is a gorgeously crafted and unputdownable exploration of female power, and what it means to be a woman at war.

Emma (Oxford world's classics, ,, 2008)
The disparity between Emma Woodhouse's self-confidence and self-knowledge, and her determination to arrange marriages for her friends while avoiding one for herself, leads to a painful series of misunderstandings for everyone who suffers from her well-meaning altruism - and with Mr Knightley being the only person of her acquaintance who has the good sense to challenge her, Emma must eventually recognize her match in every sense.

Klara and the sun (Faber & Faber, 2022)
The Sun always has ways to reach us.' From her place in the store, Klara, an Artificial Friend with outstanding observational qualities, watches carefully the behaviour of those who come in to browse, and of those who pass in the street outside. She remains hopeful a customer will soon choose her, but when the possibility emerges that her circumstances may change for ever, Klara is warned not to invest too much in the promises of humans. In Klara And The Sun, Kazuo Ishiguro looks at our rapidly-changing modern world through the eyes of an unforgettable narrator to explore a fundamental question: what does it mean to love?.

Assembly (Penguin Books, Penguin, Hamish Hamilton, 2021)
Come of age in the credit crunch. Be civil in a hostile environment. Step out into a world of Go Home vans. Go to Oxbridge, get an education, start a career. Do all the right things. Buy a flat. Buy art. Buy a sort of happiness. But above all, keep your head down. Keep quiet. And keep going. The narrator of Assembly is a Black British woman. She is preparing to attend a lavish garden party at her boyfriend's family estate, set deep in the English countryside. At the same time, she is considering the carefully assembled pieces of herself. As the minutes tick down and the future beckons, she can't escape the question: is it time to take it all apart? Assembly is a story about the stories we live within - those of race and class, safety and freedom, winners and losers. And it is about one woman daring to take control of her own story, even at the cost of her life.

The picture of Dorian Gray (Oxford world's classics, ,, 2009)
Enthralled by his own exquisite portrait, Dorian Gray exchanges his soul for eternal youth and beauty. Influenced by his friend Lord Henry Wotton, he is drawn into a corrupt double life, indulging his desires in secret while remaining a gentleman in the eyes of polite society. Only his portrait bears the traces of his decadence.

Swing time (Penguin Books, Penguin, 2017)
Two girls dream of being dancers - but only one, Tracey, has talent. The other has ideas: about rhythm and time, about black bodies and black music, what constitutes a tribe, or makes a person truly free. It's a close but complicated childhood friendship that ends abruptly in their early twenties, never to be revisited, but never quite forgotten, either. Dazzlingly energetic and deeply human, 'Swing Time' is a story about friendship and music and stubborn roots, about how we are shaped by these things and how we can survive them.

Lessons in chemistry (Penguin Books, Doubleday, 2023)
Description Not Provided

The silence of the girls (Penguin Audiobooks, Hamish Hamilton, Penguin Books, 2019)
When her city falls to the Greeks, Briseis's old life is shattered. She is transformed from queen to captive, from free woman to slave, awarded to the god-like warrior Achilles as a prize of war. And she's not alone. On the same day, and on many others in the course of a long and bitter war, innumerable women have been wrested from their homes and flung to the fighters. The Trojan War is known as a man's story: a quarrel between men over a woman, stolen from her home and spirited across the sea. But what of the other women in this story, silenced by history? What words did they speak when alone with each other, in the laundry, at the loom, when laying out the dead?

The goldfinch (Little, Brown, Abacus, 2014)
Aged 13, Theo Decker, son of a devoted mother and a reckless, largely absent father, survives an accident that otherwise tears his life apart. Alone and rudderless in New York, he is taken in by the family of a wealthy friend. He is tormented by an unbearable longing for his mother, and down the years clings to one thing that reminds him of her: a small, strangely captivating painting that ultimately draws him into the criminal underworld. As he grows up, Theo learns to glide between the drawing rooms of the rich and the dusty antiques store where he works. He is alienated and in love and his talisman, the painting, places him at the centre of a narrowing, ever more dangerous circle.

Prophet song (Oneworld, 2023)
Description Not Provided

Verity (Sphere, 2022)
Description Not Provided

Wide Sargasso Sea (Penguin classics, ,, 2011)
Inspired by Jane Eyre, Wild Sargasso Sea is Jean Rhys's powerful and compassionate story of Antoinette Cosway who is haunted by her brother's death and the madness of her mother and who is trapped in an unstable marriage.

The late Monsieur Gallet (Penguin Classics, 2013)
The circumstances of Monsieur Gallet's death all seem fake: the name the deceased was travelling under and his presumed profession, and more worryingly, his family's grief. Their haughtiness seems to hide ambiguous feelings about the hapless man. In this haunting story, Maigret discovers the appalling truth and the real crime hidden behind the surface of lies.

Hunger (Corsair, 2017)
Description Not Provided